A case of viable fetus co-existing with a complete hydatidiform mole in a twin pregnancy with successful outcome - Vikraman, Seneesh Kumar; Chandra, Vipin; Balakrishanan, Bijoy; Batra, Meenu; Kuriakose, Rekha; Kannoli, Gopinathan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Twin pregnancies with a viable fetus and co-existing complete hydatidiform mole (CHMF) are being increasingly reported in literature. It is now evident that with proper obstetric care live births can be reasonably expected. We present here such a case successfully managed at our centre with one year follow up of mother and the baby. The case highlights the role of prompt diagnosis, rational prenatal counselling, evidence based management and role of high risk obstetric and neonatal care in providing solutions to seemingly difficult situations.